Analisis Kesesuaian Implementasi Psak 109 Pada Laporan Keuangan Badan Amil Zakat Nasional (Baznas) Kabupaten Magelang - Mei Anggi Sergina; Muhamad Wahyudi (CV. ITTC INDONESIA, 2026)
This study aims to analyze the suitability of the Statement of Financial Accounting Standards (PSAK) 109 regarding Zakat and Infaq/Alms Accounting at the National Board of Zakat (BAZNAS) of Magelang Regency. The research method employed is qualitative research with a case study approach. The research data consist of information related to accounting recording techniques obtained through in-depth interviews with the staff of Division III and document analysis of the BAZNAS Magelang Regency Financial Statements. The research results regarding recognition, measurement, reporting, and disclosure indicate that the implementation of PSAK 109 has been carried out effectively, supported by a competent digital information system. This study provides recommendations to continuously maintain synchronization between internal policies and national sharia accounting standards to strengthen public transparency.